2020
DOI: 10.3390/healthcare8040506
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators of School Health Care for Students with Chronic Disease as Perceived by Their Parents: A Mixed Systematic Review

Abstract: Understanding parental perspectives through mixed systematic reviews is imperative for developing effective school health care for children and adolescents with chronic disease. A mixed systematic review was conducted to explore barriers to and facilitators of school health care for students with chronic disease as perceived by their parents. Four databases (2010–2020) were searched, following which critical appraisals were conducted to determine the validity of the selected studies using the Mixed Method Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…CF center targeted education and enhanced access to standardized materials may help to meet education-related needs with currently available clinic staff and resources. 20 This survey also highlights the need for further targeted resources to assist CF centers in assessing educational needs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CF center targeted education and enhanced access to standardized materials may help to meet education-related needs with currently available clinic staff and resources. 20 This survey also highlights the need for further targeted resources to assist CF centers in assessing educational needs.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of clarity about who is responsible for their child's care, the level of education among school staff about their child's condition, and their child's own abilities to provide care independently may contribute to stress around school. 20 Reducing redundant work is essential as many tasks, such as communicating with schools or coaching parents, may be time consuming. Additional staff training may be warranted to ensure staff are aware of these issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 A systematic Review published in Healthcare in 2020 showed that parental engagement has been a facilitator for school health care services which contrasts with findings from qualitative phase of current study that negligence of parents of some students has been a barrier for better service utilization among students. 9 As this study used non-random sampling and has small sample size i.e. 30, extreme caution must be used when evaluating results of this study.…”
Section: Discussionmentioning
confidence: 99%